Effects of in vitro cyclic dislodging on retentive force and removal torque of three overdenture attachment systems. Issue 4 (9th April 2013) - Kobayashi, Mariko; Srinivasan, Murali; Ammann, Patrick; Perriard, Jean; Ohkubo, Chikahiro; Müller, Frauke; Belser, Urs C.; Schimmel, Martin
Abstract Background Mandibular two‐implant‐retained overdentures were suggested as first choice of treatment for edentulous mandibles. However, wear of the attachments may reduce their retention and compromise long‐term clinical success. Aim The aim of this in vitro study was to compare the change in the retentive force and removal torque of three attachment systems during simulation of insertion‐removal cycles. Materials and Methods Thirty custom‐manufactured polyvinyl chloride blocks mimicking an implant‐retained overdenture using Locator®‐, spherical Dalbo®‐PLUS ‐ and SFI®‐Bar‐attachments on Straumann® RN Implants were fabricated. The samples were distributed equally into three groups which were subdivided into two sets of five blocks, one set with implants parallel to one another and the other with angulated implants (12°). All attachments were tightened to 35Ncm, while the fixation screws of the SFI®‐Bar were tightened to 15Ncm. Testing was carried out with an Instron® universal testing machine for a total of 14, 600 insertion‐removal cycles in 0.9% sodium chloride solution. Retentive forces from cycles 10, 100, 1000, 5000, 10, 000 and 14, 600 were used for the analysis. The removal torque of the attachments was measured before and at the end of the study. Statistical analysis comprised three‐way ANOVA and multiple linear regression models. Results Initially, all three attachment systems demonstrated increasing retentive forces. From cycle 5000 on, Locator®‐attachments showed lower mean retentive forces than the Dalbo®‐PLUS and SFI®‐Bar‐groups. The Dalbo®‐PLUS and SFI®‐Bar‐attachments showed a steady yet not significant increase during the whole observation period. Implant‐angulation had no significant influence on the retention forces. The final mean removal torques were significantly reduced. No complete failure was observed. Conclusions and clinical implications Within the limits of this in vitro study, it can be concluded that the investigated overdenture attachment systems are sufficiently resistant to wear. However, the Dalbo®‐Plus‐ and SFI®‐Bar‐ exhibit higher retentive capacities than the Locator®‐attachment over time. The fixation screw of the SFI®‐Bar may loosen during long‐term use, but these observations might be less important if 1‐year recall intervals are respected. An angulation of up to 12° between implants does not seem to have a significant effect on attachment wear.